Law Enforcement of Immigrated Administrative Actions on Visa Exemption Subjects (Study of Tangerang Immigration Office) - Marhala Sinaga; M. Alvi Syahrin (Polteknik Imigrasi, 2020)
This research was conducted to determine the role of the Class I Non TPI Tangerang Immigration Office in enforcing the law of immigration administrative actions against visa-free subjects in their working areas, as well as knowing the impact of enforcing the law on immigration administrative actions against visa-free subjects from an immigration perspective. This study used a qualitative normative method with a normative juridical and sociological juridical approach. This method is used to find data and describe systematically as well as factual about the form of law enforcement of immigration administration actions against visa-free subject visits. Administrative action law enforcement against visa-free subjects for visitation provided by the Class I Non TPI Tangerang Immigration Office is in the form of prevention or deterrence, imposition of fees and deportation as regulated in Law No. 6 of 2011 concerning Immigration and its derivative regulations.